Peran kader Ranting 'Aisyiyah Cabang Kota Yogyakarta dalam pemberdayaan masyarakat di bidang kesehatan - Hidayati, Ririn Wahyu; Mahmudah, Nurul (Universitas Muhammadiyah Semarang, 2020)
Health cadres have a role to assist the government in improving community health status, reducing MMR and IMR. One of his roles is to become a Posyandu cadre in Aisyiyah. But in reality, cadres have a dual role. Therefore, the researcher intends to find out how far the participation of Health cadres is in Branch Aisyiyah, Yogyakarta City Branch. This research is a qualitative study and was conducted at the Branch of ‘Aisyiyah Yogyakarta City Branch in 2017. The number of participants was taken to have a saturated answer from the cadre of isy Aisyiyah. Test analysis with content analysis. The results obtained that the cadres ‘Aisyiyah collaborated with educational institutions both ‘Aisyiyah or Muhammadiyah to provide health education, health checks and treatment. Health related activities are carried out both in the activities of recitation, social gathering, study or routine meetings of warga Aisyiyah residents. Other programs that are running are TB Knocking, assistance in taking medicine, Posyandu Elderly Sakinah, and early detection of non-communicable diseases. ‘Aisyiyah cadres play a role in mutual cooperation